Update: 2016 year in review: state advanced energy legislation - Center for the New Energy Economy, author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2017)
This supplement is provided to update readers on notable developments that followed the mid-December release of our 2016 Year in Review.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- United States